Clinical predictors of 3-month isoniazid rifapentine (3HP)-related adverse drug reactions (ADR) during tuberculosis preventive therapy (PAnDoRA-3HP study): an observational study protocol - Turyahabwe Stavia; Barbara Castelnuovo; Christine Sekaggya-Wiltshire; Kelly E Dooley; Grace Banturaki; Irene Mbabazi; Ruth Mirembe Nabisere; Lucy Alinaitwe; Brian Otaalo; Florence Aber; Juliet Nampala; Rogers Owori; et al. (BMJ Open)
Introduction Tuberculosis (TB) is the leading infectious cause of death globally. Despite WHO recommendations for TB preventive therapy (TPT), challenges persist, including incompletion of treatment and adverse drug reactions (ADRs). There is limited data on the 3-month isoniazid and rifapentine (3HP) pharmacokinetics, pharmacogenomics and their relation with ADRs. Our study aims to describe the pharmacokinetic and pharmacogenomics of 3HP used for TPT, the ADRs and their association with completion rates, and TPT outcomes, providing vital insights for TB control strategies in resource-limited settings.Methods This is an observational cohort study with a nested case–control study. We enrolled consecutive patients who had been initiated on TPT using the 3HP regimen. These are followed up biweekly and then monthly during the active phase of treatment and 3 monthly for 2 years following completion of TPT. ADR evaluation includes clinical assessment and liver function tests. Cases are selected from those who experience ADRs and controls from those who do not. Serum isoniazid and rifapentine concentrations are measured and pharmacogenomic analysis for NAT2, AADAC and CYP2E1 polymorphisms are done. Participants are followed up for 2 years to determine TPT outcomes.Analysis The safety profile of 3HP will be assessed using descriptive statistics, including proportions of patients experiencing ADRs and grade 3 or above events related to treatment. χ2 tests and regression models will determine predictors of ADRs and their impact on treatment completion. Pharmacokinetic-pharmacodynamic modelling will establish population parameters and factors influencing rifapentine and isoniazid concentrations.Ethics and dissemination Ethical approval of this study inclusive of all the appropriate documents was obtained from the Infectious Diseases Institute Research and Ethics Committee and the Uganda National Council of Science and Technology. The study adheres to legal, ethical and Good Clinical Practice (GCP) guidelines. Deidentified genotype data from 300 patients will be shared after publication. The protocol and phenotype data will be publicly accessible. Abstracts will be submitted to conferences, and a manuscript will be published poststudy.